Progress Report on the Activities of the Independent Evaluation Office. (Policy Papers; Policy Paper, 2009)
Since its last report to the IMFC in April 2009, the IEO has completed its evaluation report on IMF Involvement in International Trade Policy Issues; released the issues papers for the evaluations on the IMF's role in the run-up to the present crisis and on IMF research; and also issued the 2009 Annual Report.